The electron affinity of astatine - David Leimbach (Nature Portfolio, 2020)
Electron affinity (EA) is a key parameter in determining the chemical behavior of the elements, but challenging to measure for unstable atoms. Here the authors succeed in measuring the EA of astatine, the heaviest naturally occurring halogen, and compare it with predictions from relativistic calculations.